Development of 3D Tawaf Simulation for Hajj Training Application Using Virtual Environment - Mohd Rahim, Mohd Shafry; Fata, Ahmad Zakwan Azizul; Basori, Ahmad Hoirul; Rosman, Arief Salleh; Nizar, Tamar Jaya; Yusof, Farah Wahida Mohd (Visual Informatics: Sustaining Research and Innovations, 2011)
3D application has become very popular among people due to its capability to imitate real world environment and its interactivity to entertain users. This paper proposed an interactive training method for Hajj education in Malaysia by providing user a scene of Tawaf (one of Hajj pilgrimage rituals). Participants are provided with a flexible user control which is connected wirelessly to the system. The Tawaf simulation is created based on crowd technology and in this case we use a new method to control the movements of human character around Kaaba. Based on the user testing feedbacks, users are thrilled with the system, particularly because it is user-friendly and flexible.